ab-ac+b-c;
= (ab-ac)+(b-c)
=a(b-c)+
(b-c)
= (b-c)
(a+1)
a²-ab-2a+2b;
=(a²-ab-()2a-2b)
=a(a-b)-2(a-b)
=(a-b)(a-2)
3a-9b+2ac-6ac;
=好像有问题
3x²y+6xy-4x-8;
=(3x²y+6xy)-(4x+8)
=3xy(x+2)-4(x+2)
=(x+2)(3xy-4)
x²+3y-xy-3x;
=(x²-xy)-(3x-3y)
=x(x-y)-3(x-y)
=(x-y)(x-3)
x³+2xy-9x-18y;
=(x²+2xy)-(9x+18y)
=x(x+2y)-9(x+2y)
=(x+2y)(x-9)
(y+2)x²+(y+2)x-12y-24;
=(y+2)x²+(y+2)x-(12y+24)
=(y+2)x²+(y+2)x-12(y+2)
=(y+2)(x²+x-12)
=(y+2)(x-3)(x+4)
m²x²+n²y²-m²y²-n²x²
=(m²x²-n²x²)-(m²y²-n²y²)
=x²(m²-n²)-y²(m²-n²)
=(m²-n²)(x²-y²)
=(m-n)(m+n)(x-y)(x+y)